Challenges in managing urinary tract infection and the potential of a point-of-care test guided care in primary care: an international qualitative study. Issue 2 (2019) - Brookes-Howell, Lucy; PhD1, PhD1; Thomas-Jones, Emma; PhD2*, PhD2*; Bates, Janine; MPhil3, MPhil3; Bekkers, Marie-Jet; Brugman, Curt; Coulman, Elinor; Francis, Nick; Hashmi, Khurram; Hood, Kerenza; et al.
No abstract available